Characterization of predictors of ESBL‐producing enterobacteriaceae in urine cultures of emergency department patients. Issue 1 (14th January 2021) - Saadi, Raghad; Narayanan, Navaneeth; Ohman‐Strickland, Pamela; Zhu, Eric; McCoy, Jonathan; Wei, Grant; Kirn, Thomas J.; Bridgeman, Patrick
Abstract: Study objective: With increasing prevalence of extended‐spectrum beta‐lactamase‐producing enterobacteriaceae (ESBLE), more reliable identification of predictors for ESBLE urinary tract infection (UTI) in the emergency department (ED) is needed. Our objective was to evaluate risk factors and their predictive ability for ED patients with ESBLE UTI. Methods: This was a retrospective case‐control study at an urban academic medical center. Microbiology reports identified adult ED patients with positive urine cultures from 2015–2018. Inclusion criteria were diagnosis of UTI with monomicrobial enterobacteriaceae culture growth. Exclusions were cultures with carbapenemase‐resistant enterobacteriaceae or urinary colonization. Collected variables included demographics, comorbidities, and recent medical history. Patient disposition, urine culture susceptibilities, presence of ESBLE, empiric antibiotics, and therapy modifications were collected. Patients were stratified based on ESBLE status and analyzed via descriptive statistics. The data were divided into 2 parts: the first used to identify possible predictors of ESBLE UTI and the second used to validate an additive scoring system. Results: Of 466 patients, 16.3% had ESBLE urine culture growth and 83.7% did not; 39.5% of ESBLE patients required antibiotic therapy modification, as compared to 6.4% of ESBLE negative patients (odds ratio [OR] 9.5; confidence interval [CI] 8.9–10.1). Independent predictors of ESBLE UTI were IV antibiotics within 1 year (OR 5.4; CI 2.1–12.8), surgery within 90 days (OR 6.4; CI 1.5–27.8), and current refractory UTI (OR 8.5; CI 2.0–36.6). Conclusion: Independent predictors of ESBLE UTI in emergency department patients included IV antibiotics within 1 year, surgery within 90 days, and current refractory UTI.